2020
DOI: 10.1111/dom.13965
|View full text |Cite
|
Sign up to set email alerts
|

What have we learned about renal protection from the cardiovascular outcome trials and observational analyses with SGLT2 inhibitors?

Abstract: Over the past 5 years, sodium-glucose cotransport 2 (SGLT2) inhibitors have been increasingly regarded as glycaemic agents with cardiovascular (CV) and renal protective effects. The CV benefits of SGLT2 inhibitors have been well established in patients with type 2 diabetes (T2D) and a range of CV comorbidities at baseline. Subsequently, the renal benefits of SGLT2 inhibitors were established in the CREDENCE trial, a dedicated renal outcome trial where canagliflozin reduced the primary composite renal outcome b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 94 publications
2
21
0
Order By: Relevance
“…Subsequently, in large cardiovascular outcome trials involving participants with type 2 diabetes, empagliflozin, canagliflozin and dapagliflozin slowed the rate of decline of eGFR and reduced albuminuria with a similar eGFR trend observed for ertugliflozin. [9][10][11][12] In type 1 and type 2 diabetes, clinical studies have shown that early and reversible reductions in eGFR occurred on initiation of SGLT2 inhibitor therapy, including in those participants with good glycaemic control, [13][14][15] suggesting that SGLT2 inhibitors reduce intraglomerular pressure, which may preserve long-term kidney function. This same effect was also observed in patients with proteinuric chronic kidney disease (CKD) without diabetes, 16 providing a rationale for the use of these agents as renoprotective therapies in patients with CKD due to causes other than diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, in large cardiovascular outcome trials involving participants with type 2 diabetes, empagliflozin, canagliflozin and dapagliflozin slowed the rate of decline of eGFR and reduced albuminuria with a similar eGFR trend observed for ertugliflozin. [9][10][11][12] In type 1 and type 2 diabetes, clinical studies have shown that early and reversible reductions in eGFR occurred on initiation of SGLT2 inhibitor therapy, including in those participants with good glycaemic control, [13][14][15] suggesting that SGLT2 inhibitors reduce intraglomerular pressure, which may preserve long-term kidney function. This same effect was also observed in patients with proteinuric chronic kidney disease (CKD) without diabetes, 16 providing a rationale for the use of these agents as renoprotective therapies in patients with CKD due to causes other than diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, it was shown that a major effect of empagliflozin consisted in an acute reduction of eGFR and albuminuria, followed by long-term stability and preservation of eGFR, compared with the doubling of eGFR deterioration in the placebo group over the same period of time (3.1 years of median follow-up) [56]. Renal benefits provided by empagliflozin was observed even in patients with compromised renal function, independently from baseline HbA1c and achieved regardless of concomitant medications interacting with renal function [57,58].…”
Section: Renal Outcomes In Rcts On Sglt2 Inhibitors: State Of the Artmentioning
confidence: 99%
“…The secondary endpoint of a sustained 40% reduction in eGFR, death from renal cause, or the need for renal replacement therapy (RRT) was significantly reduced by canagliflozin (HR 0.60; 95% CI 0.47-0.77) [59]. Interestingly, the effect on CV and renal outcomes did not differ according to the presence of baseline CKD (defined as eGFR < 60 ml/min/1.73 m 2 ), albuminuria, eGFR, or BMI [58].…”
Section: Renal Outcomes In Rcts On Sglt2 Inhibitors: State Of the Artmentioning
confidence: 99%
“…Diabetic kidney disease remains the main cause of CKD, leading to end-stage kidney disease in both type 1 and type 2 diabetes [10]. Recently, sodium-glucose linked transporter-2 (SGLT2) inhibitors appeared to be the most promising nephroprotective drugs in diabetic kidney disease [11,12]; however, an antifibrotic effect has only been evidenced in animal studies [13]. There is thus a need and ample space to develop new therapeutic approaches targeting tubulointerstitial fibrosis in the kidney for combatting these pathological processes [14].…”
Section: Introductionmentioning
confidence: 99%